Sent - Yu, Kim; Big Canary Productions; Leomark Studios (Firm) ([Toronto, Ont.] : Big Canary Productions, 2016)
Sent is a documentary on Fr. Stan Fortuna, a jazz, hip hop Franciscan priest who mixes music with message and serves the poor in the South Bronx and internationally. Before his calling to the priesthood, he was a professional jazz bassist and still plays Birdland with his trio when time permits. Fr. Stan is a founding member of the Franciscan Friars of the Renewal who embrace "radical poverty" and live an ascetic lifestyle of friars in some of the poorest areas in North America, South America and Europe. Due to his talent for music, Fr. Stan has been invited to do concerts and preach the Gospel in numerous countries around the world. Sent follows Fr. Stan to various events and provides insight into his passion for music and for his faith.
Originally released as a motion picture in 2016
Editor, Ben Bratzel ; music, Fr. Stan Fortuna, CFR.
Fr. Stan Fortuna, C.F.R., Fr. Benedict Groeschel, C.F.R.
In English; with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed February 2, 2018)
Keywords: Fortuna, Stan; Rap (Music) -- Religious aspects -- Christianity; Hip-hop -- Religious aspects -- Christianity; Documentary films; Internet videos; Streaming video